Saussurea degeensis (Asteraceae, Cardueae), a new species from southwestern China - Xu, Lian-Sheng; Du, Si-Yi; Chen, You-Sheng (Phytotaxa, 2025)
Saussurea degeensis (Asteraceae, Cardueae), a new species from Hengduan Mountains is described and illustrated. The new species is referred to S. subg. Amphilaena based on its obvious purple bracts, uncolored phyllary apices, and simple inflorescence. Our molecular phylogenetic analyses further indicated that the new species is most related to S. acutisquama, S. iodostegia, S. nigrescens, S. superba, S. tatsienensis, S. veitchiana, and S. wenchengiae. Morphologically, the new species is similar to S. nigrescens in obvious purple bracts, but differs by bigger leaves with crisped margins, more numerous bracts, and not obtuse phyllary apex.